Inclusive Education Based on Humanistic Learning: Teachers' Innovation Ability in Learning at SMAN 4 Palangka Raya - Lilis Rahmawati; Hamdanah Hamdanah; Surawan Surawan (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Background: Teacher innovation and the implementation of humanistic learning in inclusive schools are important to ensure the creation of learning that respects diversity and meets the individual needs of all learners. Aim: This study aims to analyze PAI teachers' innovations in implementing inclusive education based on humanistic learning to improve the quality of inclusive and learner-centered learning. Method: This study used descriptive qualitative research with data collection techniques in the form of interviews. Results and Dıscussion: The results of this study indicated that PAI teachers' innovation is running well (89.78%) in inclusive education because PAI teachers are able to design and implement innovative learning strategies, including curriculum adaptation, use of relevant learning media, and approaches that pay attention to the special needs of inclusive learners, while humanistic-based learning is running very well (91.36%) in inclusive education because PAI teachers have successfully implemented humanistic learning principles, such as humanizing learners. This is illustrated in the learning process when conducting direct observation in the classroom and in the school environment that every teacher pays attention to every learner's needs. This successful implementation reflects the commitment of PAI teachers in encouraging the creation of a learning atmosphere that is full of empathy, respect for diversity, and supports the holistic development of learners, both in academic and non-academic aspects. These results are evidence that innovation and humanistic approaches are very relevant to support quality inclusive education.